2020
DOI: 10.3390/cancers12020432
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Antitumor Activity of Low Molecular Weight Heparins in Pancreatic Adenocarcinomas

Abstract: Immune checkpoint inhibitors have revolutionized cancer treatment in the last decade. Despite the progress in immunotherapy, most pancreatic cancer patients still do not derive benefit when receiving immune-based therapies. Recently, resistance mechanisms to immune therapies have been mainly focused on tumor microenvironment properties. Pancreatic cancer is considered one of the most lethal and difficult to treat tumors due to its highly immunosuppressive and desmoplastic microenvironment. Low molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Tinzaparin exerts its anti-neoangiogenic activity as it appears to stimulate more production of tissue factor pathway inhibitor (TFPI) by epithelial cells than any other low molecular weight heparin, inhibiting tissue factor (TF) and consequently VEGFR. TFPI works by blocking the activation of protease activated receptors 2 (PAR2), the activation of which plays an important role in the metastatic potential of this type of cancer [14]. In vitro experiments have shown that the triple combination with tinzaparin, nab-paclitaxel and gemcitabine, decreases the protein levels of VEGFR2 in PC cell lines with mutant KRAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tinzaparin exerts its anti-neoangiogenic activity as it appears to stimulate more production of tissue factor pathway inhibitor (TFPI) by epithelial cells than any other low molecular weight heparin, inhibiting tissue factor (TF) and consequently VEGFR. TFPI works by blocking the activation of protease activated receptors 2 (PAR2), the activation of which plays an important role in the metastatic potential of this type of cancer [14]. In vitro experiments have shown that the triple combination with tinzaparin, nab-paclitaxel and gemcitabine, decreases the protein levels of VEGFR2 in PC cell lines with mutant KRAS.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that LMWHs can affect circulating tumor cells and the tumor microenvironment (TME) through various mechanisms including the effects of heparan sulfate proteoglycans/heparanase on metastasis formation, angiogenesis/tumor vasculature, and immune-suppressive/therapy-resistant TME. This ability of LMWHs to interfere with various aspects of the tumor microenvironment could, ultimately, lead to better patient outcomes [14]. There have been several experimental studies with cell lines, tumor tissue samples, and animal models in various types of cancers that have demonstrated the antitumor, anti-metastatic, and chemo-resistance reversal effect of LMWHs [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a range of studies suggest that heparin derivatives and conjugates can inhibit tumor growth and metastasis by suppressing many tumor-related factors ( Figure 1 ) [ 1 , 10 , 11 ]. Heparin-based biomolecules are able to bind to vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), P-selectin, CXC motif chemokine ligand 12 (CXCL12, also called stromal-derived factor-1; SDF-1), and heparanase, affecting cell migration, adhesion, and angiogenesis [ 15 , 16 , 17 ]. Therefore, in this review, we summarize the current advances and challenges in the development of heparin-related biomolecules such as heparin derivatives and conjugates for their successful clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In human carcinomas therefore, the primary target of anti-cancer compounds is the central sensor for nutrient and energy availability which regulates cell cycle, growth and proliferation (Luengo et al 2017 ; Zhang et al 2018 ). Cancer treatments have largely proceeded through surgery, radiotherapy, immunotherapy and chemotherapy employing diverse agents including inorganic (Jaros et al 2019 ; Chen et al 2020 ) and organic compounds or a combination of both (Bokas et al 2020 ). Peptide molecules from different biological sources including plants (de Oliveira et al 2015 ; Eswaraiah et al 2020 ), animals (Elrayess et al 2020 ) and microorganisms (Sereena and Sebastian 2020 ; Harish et al 2020 ) have demonstrated precision in target identification and activity, and have therefore received tremendous attention as key components of anti-cancer chemotherapy in recent years.…”
Section: Introductionmentioning
confidence: 99%